Discrete element modeling of vibrating tillage tools. Issue 2 (20th April 2015) - Keppler, Istvan; Hudoba, Zoltan; Oldal, Istvan; Csatar, Attila; Fenyvesi, Laszlo
Abstract : Purpose: – The analysis of the effect of tool vibrations on the measured and simulated draught forces of cultivator tools. This paper aims to discuss this issue. Design/methodology/approach: – Soil bin measurements and discrete element method (DEM)-based simulations. Findings: – The soil-tool interaction induced free vibrations of cultivator tools have significant impact on the measured draught force, and the simulations made by using vibrating tools give similar results. Research limitations/implications: – Accurate calibration of discrete element model parameters can be done based on the reproduction of the whole Mohr-Coulomb failure line. Draught force ratio – velocity ratio values seem to be independent of tool geometry and soil conditions in case of velocity ratio higher than 2. Practical implications: – DEM-based numerical simulations can be used for modeling the effect of tool vibration on the draught force values. During discrete element simulations of soil-tool interaction, the effect of tool vibration may not be neglected. Originality/value: – The paper demonstrates that during the discrete element modelling of the soil-tool interaction, the tool vibration phenomenon should not be neglected.